Skip to main content

New construction of type 2 degenerate central Fubini polynomials with their certain properties

Abstract

Kim et al. (Proc. Jangjeon Math. Soc. 21(4):589–598, 2018) have studied the central Fubini polynomials associated with central factorial numbers of the second kind. Motivated by their work, we introduce degenerate version of the central Fubini polynomials. We show that these polynomials can be represented by the fermionic p-adic integral on \(\mathbb{Z}_{p}\). From the fermionic p-adic integral equations, we derive some new properties related to degenerate central factorial numbers of the second kind and degenerate Euler numbers of the second kind.

Introduction

Let p be chosen as a fixed odd prime number. We make use of the following notations: \(\mathbb{Z}_{p}\), \(\mathbb{Q}_{p}\), \(\mathbb{C}_{p}\), \(\mathbb{N} \), \(\mathbb{N} _{0}\) and \(\mathbb{R} \) denote the ring of p-adic integers, the field of p-adic rational numbers, the completion of an algebraic closure of \(\mathbb{Q}_{p}\), the set of natural number, the set of natural numbers containing zero and the set of real numbers, respectively. We say that \(\vert \cdot \vert _{p}\) is normalized if \(\vert {p} \vert _{p}=p^{-1}\). Let \(C ( \mathbb{Z} _{p} ) \) be the space of \(\mathbb{C} _{p}\)-valued continuous functions on \(\mathbb{Z} _{p}\). For \(f\in C ( \mathbb{Z} _{p} ) \), the fermionic p-adic integral of a function f was originally constructed by Kim [12] as follows:

$$\begin{aligned} I_{-1} ( f ) :=& \int _{\mathbb{Z}_{p}}f(x)\,d\mu _{-1}(x) \\ =&\lim_{n\rightarrow \infty }\sum_{a=0}^{p^{n}-1}f(a) \mu _{-1}\bigl(a+p^{n} \mathbb{Z}_{p}\bigr) \\ =&\lim_{n\rightarrow \infty }\sum_{a=0}^{p^{n}-1}f(a) (-1)^{a}. \end{aligned}$$
(1)

Here \(I_{-1}\) is used symbolically due to its fermionic distribution \(\mu _{-1}\). It follows from (1) that

$$ I_{-1} ( f_{1} ) +I_{-1} ( f ) =2f(0) \quad \text{(see [12])} $$
(2)

with the assumption \(f_{1} ( x ) :=f ( x+1 ) \). For more information about the applications of p-adic integrals, one can refer to [4, 8, 9, 14, 17, 22] and the references cited therein.

Very recently, Kim et al. [20] showed that the Fubini polynomials can be represented by the fermionic p-adic integral on \(\mathbb{Z}_{p}\) as follows:

$$ \int _{\mathbb{Z}_{p}}\bigl(x\bigl(1-e^{t}\bigr) \bigr)^{y}\,d\mu _{-1}(y)= \frac{2}{1-x(e^{t}-1)}=2\sum _{n=0}^{\infty }F_{n}(x) \frac{t^{n}}{n!}. $$
(3)

For more information about the Fubini polynomials, one can look at the references [5, 10, 24]. The Stirling numbers of the second kind are defined by (see [11])

$$ x^{n}=\sum_{k=0}^{n}S_{2}(n,k) (x)_{k}, $$
(4)

where

$$ (x)_{n}= \textstyle\begin{cases} x(x-1)\cdots (x-n+1), & \text{when }n\geq 1, \\ 1, & \text{when }n=0,\end{cases}$$

or equivalently by

$$ \sum_{n=k}^{\infty }S_{2}(n,k) \frac{t^{n}}{n!}= \frac{(e^{t}-1)^{k}}{k!} \quad (k\geq 0). $$
(5)

Let \(\lambda \neq 0\) be any real numbers. Carlitz [1] introduced the degenerate Bernoulli polynomials by means of the following generating function:

$$ \sum_{n=0}^{\infty }\beta _{n}(x; \lambda )\frac{t^{n}}{n!}= \frac{t}{(1+\lambda t)^{\frac{1}{\lambda }}-1}(1+\lambda t)^{ \frac{x}{\lambda }}. $$
(6)

When \(x=0\) in (6), \(\beta _{n}(\lambda )=:\beta _{n}(0;\lambda )\) are the degenerate Bernoulli numbers. It is clear from (6) that

$$ \lim_{\lambda \rightarrow 0}\beta _{n}(x;\lambda ):=B_{n}(x) \quad ( n\in \mathbb{N} _{0} ) , $$

where \(B_{n} ( x ) \) are the Bernoulli polynomials given by

$$ \sum_{n=0}^{\infty }B_{n}(x) \frac{t^{n}}{n!}=\frac{t}{e^{t}-1}e^{xt} ,\quad \textit{cf. } \mbox{[1]}. $$

Parallel to (6), the degenerate Euler polynomials are defined by means of the following generating function:

$$ \sum_{n=0}^{\infty }\mathit{E}_{n}(x; \lambda ) \frac{t^{n}}{n!}=\frac{2}{(1+\lambda t)^{\frac{1}{\lambda }}+1}(1+\lambda t)^{ \frac{x}{\lambda }}\quad ( 0\neq \lambda \in \mathbb{R} ) \text{ (see [1])}. $$
(7)

When \(x=0\) in (9), \(\mathit{E}_{n}(\lambda )=:\mathit{E}_{n}(0;\lambda )\) are the degenerate Euler numbers.

For \(0\neq \lambda \in \mathbb{R} \), it is worth noting from [16, 21] that

$$\begin{aligned} e_{\lambda }^{x}(t) :=&(1+\lambda t)^{\frac{x}{\lambda }} \\ =&\sum_{n=0}^{\infty } \biggl( \frac{x}{\lambda } \biggr) _{n} \lambda ^{n}\frac{t^{n}}{n!} \\ =&\sum_{n=0}^{\infty }(x)_{n,\lambda } \frac{t^{n}}{n!}, \end{aligned}$$
(8)

where

$$ (x)_{0,\lambda }=1, \quad\quad (x)_{n,\lambda }:=x ( x-\lambda ) ( x-2 \lambda ) \cdots \bigl( x- ( n-1 ) \lambda \bigr) \quad ( n\geq 1 ) \text{ see [19].} $$

The degenerate Euler numbers of the second kind are given by

$$ {\operatorname{sech}}_{\lambda }(t)=\frac{2}{e_{\lambda }(t)+e_{\lambda }^{-1}(t)}=\sum _{n=0}^{\infty }E_{n,\lambda }^{\ast } \frac{t^{n}}{n!} . $$
(9)

It is obvious that

$$ \lim_{\lambda \rightarrow 0}E_{n,\lambda }^{\ast }:=E_{n}^{\ast } , $$

where \(E_{n}^{\ast }\) are the Euler numbers of the second kind given by

$$ \frac{2}{e^{t}+e^{-t}}=\sum_{n=0}^{\infty }E_{n}^{\ast } \frac{t^{n}}{n!},\quad \textit{cf. }\mbox{[3]}. $$

By (5) and (6), the degenerate Stirling polynomials of the second kind are defined by the generating function

$$ \sum_{n=k}^{\infty }S_{2,\lambda }^{(x)}(n,k) \frac{t^{n}}{n!}=\frac{(e_{\lambda }(t)-1)^{k}}{k!}e_{\lambda }^{x}(t), $$
(10)

where \(x\in \mathbb{R}\), and k is a nonnegative integer (see [13]). In the case \(x=0\), \(S_{2,\lambda }^{(0)}(n,k):=S_{2,\lambda }(n,k)\) are the degenerate Stirling numbers of the second kind, cf. [14, 6, 7].

Since

$$ \lim_{\lambda \rightarrow 0}e_{\lambda }(t)=e^{t} $$

we have

$$ \lim_{\lambda \rightarrow 0}S_{2,\lambda }^{(x)}(n,k):=S_{2}^{(x)}(n,k) , $$

where \(S_{2}^{(x)}(n,k)\) are the Stirling polynomials of the second kind given by

$$ \sum_{n=k}^{\infty }S_{2}^{(x)}(n,k) \frac{t^{n}}{n!}= \frac{e^{xt}(e^{t}-1)^{k}}{k!}. $$

The central factorial numbers of the second kind, denoted by \(T(j,k)\) with the conditions \(j\geqslant 0\) and \(k\geq 0\), are defined by

$$ x^{j}=\sum_{k=0}^{j}T(j,k)x^{[k]} \quad \text{(see [11])}, $$
(11)

where

$$ x^{[k]}= \textstyle\begin{cases} x(x+\frac{k}{2}-1)(x+\frac{k}{2}-2)\cdots (x-\frac{k}{2}+1), & \text{when }k\geqslant 1, \\ 1, & \text{when }k=0\end{cases}$$

or equivalently by

$$ \frac{1}{k!} \bigl( e^{\frac{z}{2}}-e^{-\frac{z}{2}} \bigr) ^{k}= \sum_{j=k}^{\infty }T(j,k) \frac{z^{j}}{j!} \quad \text{(see [11, 23])}. $$
(12)

Kim–Kim [15] introduced the degenerate central factorial polynomials of the second kind as follows:

$$ \sum_{j=k}^{\infty }T_{\lambda }(j,k| x) \frac{z^{j}}{j!}= \frac{1}{k!} \bigl( e_{\lambda }^{\frac{1}{2}} ( z ) -e_{\lambda }^{ \frac{-1}{2}} ( z ) \bigr) ^{k}e_{\lambda }^{x} ( t ) , $$
(13)

where k is a nonnegative integer. The case \(x=0\) yields \(T_{\lambda }(j,k)=:T_{\lambda }(j,k| 0)\) that are the degenerate central factorial numbers of the second kind.

This paper is organized as follows. In Sect. 2, we consider the generating function of type 2 degenerate central Fubini polynomials and give some properties of these numbers and polynomials. In Sect. 3, we introduce degenerate central Fubini numbers and polynomials and derive some properties of these polynomials by using p-adic fermionic integrals on \(\mathbb{Z}_{p} \). In Sect. 4, we introduce type 2 degenerate central Fubini polynomials of two variables and construct some properties of these polynomials. Also, these polynomials are closely related to degenerate central factorial numbers of the second kind and degenerate Euler numbers of the second kind.

On type 2 degenerate central Fubini polynomials

In this section, we assume that \(\lambda \neq 0\) is any real number. We begin with giving type 2 degenerate central Fubini polynomials as follows:

$$ \sum_{n=0}^{\infty }F_{n,\lambda }^{(C)}(x) \frac{t^{n}}{n!}= \frac{1}{1-x(e_{\lambda }^{\frac{1}{2}}(t)-e_{\lambda }^{-\frac{1}{2}}(t))} . $$
(14)

Note that

$$ \lim_{\lambda \rightarrow 0}\sum_{n=0}^{\infty }F_{n, \lambda }^{(C)}(x) \frac{t^{n}}{n!}:=\sum_{n=0}^{\infty }F_{n}^{(C)}(x) \frac{t^{n}}{n!}=\frac{1}{1-x(e^{\frac{t}{2}}-e^{-\frac{t}{2}})} \quad \text{(see [11])}. $$

By (14), one may see that

$$\begin{aligned} \sum_{n=0}^{\infty }F_{n,\lambda }^{(C)}(x) \frac{t^{n}}{n!} =&\frac{1}{1-x(e_{\lambda }^{\frac{1}{2}}(t)-e_{\lambda }^{-\frac{1}{2}}(t))} \\ =&\sum_{k=0}^{\infty }x^{k} \bigl(e_{\lambda }^{\frac{1}{2}}(t)-e_{ \lambda }^{-\frac{1}{2}}(t) \bigr)^{k} \\ =&\sum_{k=0}^{\infty }x^{k}k!\sum _{n=k}^{\infty }T_{ \lambda }(n,k) \frac{t^{n}}{n!} \\ =&\sum_{n=0}^{\infty } \Biggl( \sum _{k=0}^{n}x^{k}k!T_{ \lambda }(n,k) \Biggr) \frac{t^{n}}{n!}. \end{aligned}$$

Thus, we state the following theorem.

Theorem 2.1

Let n be a nonnegative integer. Then the following holds:

$$ F_{n,\lambda }^{(C)}(x)=\sum_{k=0}^{n}x^{k}k!T_{\lambda }(n,k) . $$
(15)

The degenerate ordered Bell numbers are defined by the generating function to be

$$ \frac{1}{1-2\sinh _{2\lambda }(\frac{t}{2})}=\sum_{n=0}^{ \infty }b_{n,\lambda } \frac{t^{n}}{n!}, $$
(16)

where

$$ \sinh _{\lambda }(t)=\frac{e_{\lambda }(t)-e_{\lambda }^{-1}(t)}{2} , \quad \textit{cf. }\mbox{[3]}. $$

Corollary 2.1

Taking \(x=1\) in (15) gives

$$ F_{n,\lambda }^{(C)}(1):=b_{n,\lambda }=\sum _{k=0}^{n}k!T_{ \lambda }(n,k)\quad ( n\geq 0 ) . $$

By (14), we have

$$\begin{aligned} \sum_{n=0}^{\infty }F_{n,\lambda }^{(C)}(x) \frac{t^{n}}{n!} =&\frac{1}{1-xe_{\lambda }^{-\frac{1}{2}}(t)(e_{\lambda }(t)-1)} \\ =&\sum_{k=0}^{\infty }x^{k}e_{\lambda }^{-\frac{k}{2}}(t) \bigl(e_{ \lambda }(t)-1\bigr)^{k} \\ =&\sum_{k=0}^{\infty }x^{k}k!e_{\lambda }^{-\frac{k}{2}}(t) \frac{(e_{\lambda }(t)-1)^{k}}{k!} \\ =&\sum_{k=0}^{\infty }x^{k}k!\sum _{n=k}^{\infty }S_{2, \lambda }^{ ( \frac{-k}{2} ) }(n,k) \frac{t^{n}}{n!} \\ =&\sum_{n=0}^{\infty } \Biggl( \sum _{k=0}^{n}x^{k}k!S_{2, \lambda }^{ ( \frac{-k}{2} ) }(n,k) \Biggr) \frac{t^{n}}{n!}. \end{aligned}$$
(17)

Thus, we state the following theorem.

Theorem 2.2

Let n be a nonnegative integer. Then the following relation holds true:

$$ F_{n,\lambda }^{(C)}(x)=\sum_{k=0}^{n}x^{k}k!S_{2,\lambda }^{ ( \frac{-k}{2} ) }(n,k). $$

By (9), we have

$$\begin{aligned} \sum_{n=0}^{\infty }E_{n,\lambda }^{\ast } \frac{t^{n}}{n!} =&\frac{2}{e_{\lambda } ( t ) +e_{\lambda }^{-1} ( t ) } \\ =&\frac{2}{2+(e_{\lambda }^{\frac{1}{2}}(t)-e_{\lambda }^{-\frac{1}{2}}(t))^{2}} \\ =&\sum_{k=0}^{\infty } \biggl( - \frac{1}{2} \biggr) ^{k}\bigl(e_{ \lambda }^{\frac{1}{2}}(t)-e_{\lambda }^{-\frac{1}{2}}(t) \bigr)^{2k} \\ =&\sum_{k=0}^{\infty } \biggl( - \frac{1}{2} \biggr) ^{k}(2k)! \sum_{n=2k}^{\infty }T_{\lambda }(n,2k) \frac{t^{n}}{n!} \\ =&\sum_{n=0}^{\infty } \Biggl( \sum _{k=0}^{ [ \frac{n}{2} ] } \biggl( -\frac{1}{2} \biggr) ^{k}(2k)!T_{\lambda }(n,2k) \Biggr) \frac{t^{n}}{n!}. \end{aligned}$$

Thus we arrive at the following theorem.

Theorem 2.3

Let n be a nonnegative integer. Then the following relation between \(E_{n,\lambda }^{\ast }\) and \(T_{\lambda }(n,2k)\) holds true:

$$ E_{n,\lambda }^{\ast }=\sum_{k=0}^{ [ \frac{n}{2} ] } \biggl( -\frac{1}{2} \biggr) ^{k}(2k)!T_{\lambda }(n,2k) . $$

The following computations based on (14) show that

$$\begin{aligned} \sum_{n=0}^{\infty }F_{n,\lambda }^{(C)}(x) \frac{t^{n}}{n!} =&\frac{1}{1-x(e_{\lambda }^{\frac{1}{2}}(t)-e_{\lambda }^{-\frac{1}{2}}(t))} \\ =&\sum_{k=0}^{\infty }x^{k} \bigl( e_{\lambda }^{ \frac{1}{2}}(t)-e_{\lambda }^{-\frac{1}{2}}(t) \bigr) ^{k} \\ =&\sum_{k=0}^{\infty }x^{k}\sum _{l=0}^{k} \binom{k}{l}(-1)^{k-l}e_{\lambda }^{(l-\frac{k}{2})} ( t ) \\ =&\sum_{k=0}^{\infty }x^{k}\sum _{l=0}^{k} \binom{k}{l}(-1)^{k-l} \sum_{n=0}^{\infty } \biggl( l-\frac{k}{2} \biggr) _{n, \lambda }\frac{t^{n}}{n!} \\ =&\sum_{n=0}^{\infty } \Biggl( \sum _{k=0}^{\infty }x^{k} \sum _{l=0}^{k}\binom{k}{l}(-1)^{k-l} \biggl( l-\frac{k}{2} \biggr) _{n,\lambda } \Biggr) \frac{t^{n}}{n!}. \end{aligned}$$

Thus, we obtain the following theorem.

Theorem 2.4

Let n be a nonnegative integer. Then the following explicit summation formula holds true:

$$ F_{n,\lambda }^{(C)}(x)=\sum_{k=0}^{\infty }x^{k} \sum_{l=0}^{k}\binom{k}{l}(-1)^{k-l} \biggl( l-\frac{k}{2} \biggr) _{n,\lambda } . $$

On type 2 degenerate central Fubini polynomials by the fermionic p-adic integral on \(\mathbb{Z}_{p}\)

In this section, let us assume that \(\lambda \in \mathbb{C} _{p}\) and \(t\in \mathbb{C}_{p}\) with the condition \(\vert \lambda t \vert _{p}< p^{-\frac{1}{p-1}}\). By (3) and (14), it becomes

$$\begin{aligned} \int _{\mathbb{Z}_{p}}\bigl(x\bigl(e_{\lambda }^{\frac{-1}{2}}(t)-e_{\lambda }^{ \frac{1}{2}}(t) \bigr)\bigr)^{y}\,d\mu _{-1}(y) =&\frac{2}{1-x(e_{\lambda }^{\frac{1}{2}}(t)-e_{\lambda }^{-\frac{1}{2}}(t))} \\ =&2\sum_{n=0}^{\infty }F_{n,\lambda }^{(C)}(x) \frac{t^{n}}{n!}. \end{aligned}$$
(18)

From (18), we have

$$\begin{aligned} 2\sum_{n=0}^{\infty }F_{n,\lambda }^{(C)}(x) \frac{t^{n}}{n!} =& \int _{\mathbb{Z}_{p}}\bigl(x\bigl(e_{\lambda }^{\frac{-1}{2}}(t)-e_{\lambda }^{ \frac{1}{2}}(t) \bigr)\bigr)^{y}\,d\mu _{-1}(y) \\ =& \int _{\mathbb{Z}_{p}}\bigl(-x\bigl(e_{-\lambda }^{\frac{-1}{2}}(-t)-e_{- \lambda }^{\frac{1}{2}}(-t) \bigr)\bigr)^{y}\,d\mu _{-1}(y) \\ =&2\sum_{n=0}^{\infty }(-1)^{n}F_{n,-\lambda }^{(C)}(-x) \frac{t^{n}}{n!}. \end{aligned}$$

Thus, we get the following theorem.

Theorem 3.1

Let n be a nonnegative integer. The following symmetric relation holds true:

$$ F_{n,\lambda }^{(C)}(x)=(-1)^{n}F_{n,-\lambda }^{(C)}(-x). $$

By (2) and (14), we have

$$ \int _{\mathbb{Z}_{p}}\bigl(x\bigl(e_{\lambda }^{-\frac{1}{2}}(t)-e_{\lambda }^{ \frac{1}{2}}(t) \bigr)\bigr)^{y+1}\,d\mu _{-1}(y)+ \int _{\mathbb{Z}_{p}}\bigl(x\bigl(e_{\lambda }^{- \frac{1}{2}}(t)-e_{\lambda }^{\frac{1}{2}}(t) \bigr)\bigr)^{y}\,d\mu _{-1}(y)=2. $$
(19)

By (19), we get

$$ x\bigl(e_{\lambda }^{-\frac{1}{2}}(t)-e_{\lambda }^{\frac{1}{2}}(t) \bigr) \frac{2}{1-x(e_{\lambda }^{\frac{1}{2}}(t)-e_{\lambda }^{-\frac{1}{2}}(t))}+ \frac{2}{1-x(e_{\lambda }^{\frac{1}{2}}(t)-e_{\lambda }^{-\frac{1}{2}}(t))}=2 . $$
(20)

It follows from (20) that

$$\begin{aligned} 1 =&x \Biggl( \sum_{n=0}^{\infty } \biggl( \biggl( - \frac{1}{2} \biggr) _{n,\lambda }- \biggl( \frac{1}{2} \biggr) _{n, \lambda } \biggr) \frac{t^{n}}{n!} \Biggr) \Biggl( \sum _{n=0}^{\infty }F_{n,\lambda }^{(C)}(x) \frac{t^{n}}{n!} \Biggr) +\sum_{n=0}^{\infty }F_{n,\lambda }^{(C)}(x) \frac{t^{n}}{n!} \\ =&\sum_{n=0}^{\infty } \Biggl[ x\sum _{m=0}^{n} \binom{n}{m}F_{m,\lambda }^{(C)}(x) \biggl( \biggl( -\frac{1}{2} \biggr) _{n-m, \lambda }- \biggl( \frac{1}{2} \biggr) _{n-m,\lambda } \biggr) +F_{n, \lambda }^{(C)}(x) \Biggr] \frac{t^{n}}{n!} \\ =&\sum_{n=0}^{\infty } \Biggl[ F_{n,\lambda }^{(C)}(x)+x \sum_{m=0}^{n} \binom{n}{m}F_{m,\lambda }^{(C)}(x) \biggl( \biggl( - \frac{1}{2} \biggr) _{n-m,\lambda }- \biggl( \frac{1}{2} \biggr) _{n-m,\lambda } \biggr) \Biggr] \frac{t^{n}}{n!}. \end{aligned}$$

Thus we state the following theorem.

Theorem 3.2

For \(n>0\), we have

$$ F_{n,\lambda }^{(C)}(x)=-x\sum_{m=0}^{n} \binom{n}{m}F_{m, \lambda }^{(C)}(x) \biggl( \biggl( - \frac{1}{2} \biggr) _{n-m,\lambda }- \biggl( \frac{1}{2} \biggr) _{n-m,\lambda } \biggr) . $$
(21)

For \(n\in \mathbb{N}\), by (21), we get

$$\begin{aligned} F_{n,\lambda }^{(C)}(x) =&x\sum_{m=0}^{n} \binom{n}{m}F_{m, \lambda }^{(C)}(x) \biggl( \biggl( \frac{1}{2} \biggr) _{n-m,\lambda }- \biggl( -\frac{1}{2} \biggr) _{n-m,\lambda } \biggr) \\ =&x\sum_{m=0}^{n-1}\binom{n}{m}F_{m,\lambda }^{(C)}(x) \biggl( \biggl( \frac{1}{2} \biggr) _{n-m,\lambda }- \biggl( - \frac{1}{2} \biggr) _{n-m,\lambda } \biggr) \\ =&x\sum_{m=0}^{n-2}\binom{n}{m}F_{m,\lambda }^{(C)}(x) \biggl( \biggl( \frac{1}{2} \biggr) _{n-m,\lambda }- \biggl( - \frac{1}{2} \biggr) _{n-m,\lambda } \biggr) +xnF_{n-1,\lambda }^{(C)}(x) . \end{aligned}$$

Thus we get the following corollary.

Corollary 3.1

Let n be a positive integer satisfying with \(n\geq 2\). Then the following equation holds true:

$$ F_{n,\lambda }^{(C)}(x)-xnF_{n-1,\lambda }^{(C)}(x)=x\sum _{m=0}^{n-2}\binom{n}{m}F_{m,\lambda }^{(C)}(x) \biggl( \biggl( \frac{1}{2} \biggr) _{n-m,\lambda }- \biggl( - \frac{1}{2} \biggr) _{n-m,\lambda } \biggr) . $$

On type 2 degenerate central Fubini polynomials of two variable

In this section, we assume that \(\lambda \neq 0\) is any real number. We are now in a position to state the type 2 degenerate central Fubini polynomials of two variable as follows:

$$ \sum_{n=0}^{\infty }F_{n,\lambda }^{(C)}(x;y) \frac{t^{n}}{n!}= \frac{1}{1-y(e_{\lambda }^{\frac{1}{2}}(t)-e_{\lambda }^{-\frac{1}{2}}(t))}e_{\lambda }^{x}(t). $$
(22)

When \(x=0\), \(F_{n,\lambda }^{(C)}(0;y)=F_{n,\lambda }^{(C)}(y)\), \(F_{n,\lambda }^{(C)}(0;1)=F_{n,\lambda }^{(C)} ( 1 ) \) are called the central Fubini polynomials and the central Fubini numbers, respectively.

Since

$$ \lim_{\lambda \rightarrow 0}e_{\lambda }^{x} ( t ) =e^{xt}= \sum_{n=0}^{\infty } \frac{x^{n}t^{n}}{n!}, $$

it is not difficult to show that

$$ \lim_{\lambda \rightarrow 0}\sum_{n=0}^{\infty }F_{n, \lambda }^{(C)}(x;y) \frac{t^{n}}{n!}= \frac{1}{1-y(e^{\frac{t}{2}}-e^{-\frac{t}{2}})}e^{xt}, $$

which is the generating function of the central Fubini polynomials of two variables; see [18].

From (22), we have

$$\begin{aligned} \sum_{n=0}^{\infty }F_{n,\lambda }^{(C)}(x;y) \frac{t^{n}}{n!} =&\frac{1}{1-y(e_{\lambda }^{\frac{1}{2}}(t)-e_{\lambda }^{-\frac{1}{2}}(t))}e_{\lambda }^{x}(t) \\ =& \Biggl( \sum_{k=0}^{\infty }F_{k,\lambda }^{(C)}(y) \frac{t^{k}}{k!} \Biggr) \Biggl( \sum_{n=0}^{\infty }(x)_{n,\lambda } \frac{t^{n}}{n!} \Biggr) \\ =&\sum_{n=0}^{\infty } \Biggl( \sum _{k=0}^{n} \binom{n}{k}F_{k,\lambda }^{(C)}(y) (x)_{n-k,\lambda } \Biggr) \frac{t^{n}}{n!} . \end{aligned}$$

Thus, we obtain the following theorem.

Theorem 4.1

Let n be a nonnegative integer. Then the following identity holds:

$$ F_{n,\lambda }^{(C)}(x;y)=\sum_{k=0}^{n} \binom{n}{k}F_{k, \lambda }^{(C)}(y) (x)_{n-k,\lambda }. $$

Changing t to \(\frac{e^{\lambda t}-1}{\lambda }\) in (22) gives

$$\begin{aligned} \frac{1}{1-y(e^{\frac{t}{2}}-e^{-\frac{t}{2}})}e^{xt} =&\sum_{k=0}^{\infty }F_{k,\lambda }^{(C)}(x;y) \lambda ^{-k} \frac{(e^{\lambda t}-1)^{k}}{k!} \\ =&\sum_{n=0}^{\infty } \Biggl( \sum _{k=0}^{n}F_{k, \lambda }^{(C)}(x;y)\lambda ^{n-k}S_{2}(n,k) \Biggr) \frac{t^{n}}{n!} . \end{aligned}$$
(23)

By (5) and (23), we have the following theorem.

Theorem 4.2

Let n be a nonnegative integer. Then the following identity holds:

$$ F_{n}^{(C)}(x;y)=\sum_{k=0}^{n} \lambda ^{n-k}F_{k,\lambda }^{(C)}(x;y)S_{2}(n,k) . $$

By (22), we see that

$$\begin{aligned} e_{\lambda }^{x}(t)&= \bigl( 1-y\bigl(e_{\lambda }^{\frac{1}{2}}(t)-e_{ \lambda }^{-\frac{1}{2}}(t) \bigr) \bigr) \sum_{n=0}^{\infty }F_{n, \lambda }^{(C)}(x;y) \frac{t^{n}}{n!} \\ &= \Biggl( \sum_{n=0}^{\infty }F_{n,\lambda }^{(C)}(x;y)- \sum_{k=0}^{n}\binom{n}{k} \biggl( yF_{n-k,\lambda }^{(C)}(x;y) \biggl( \biggl( \frac{1}{2} \biggr) _{k,\lambda }- \biggl( - \frac{1}{2} \biggr) _{k,\lambda } \biggr) \biggr) \Biggr) \frac{t^{n}}{n!} . \end{aligned}$$
(24)

By (8) and (24), we obtain the following theorem.

Theorem 4.3

Let n be a nonnegative integer. The following formula holds true:

$$ (x)_{n,\lambda }=F_{n,\lambda }^{(C)}(x;y)-y\sum _{k=0}^{n} \binom{n}{k}F_{n-k,\lambda }^{(C)}(x;y) \biggl( \biggl( \frac{1}{2} \biggr) _{k, \lambda }- \biggl( - \frac{1}{2} \biggr) _{k,\lambda } \biggr) . $$

Let us observe that

$$\begin{aligned}& \frac{e_{\lambda }^{x_{1}}(t)}{1-y_{1}(e_{\lambda }^{\frac{1}{2}}(t)-e_{\lambda }^{-\frac{1}{2}}(t))} \frac{e_{\lambda }^{x_{2}}(t)}{1-y_{2}(e_{\lambda }^{\frac{1}{2}}(t)-e_{\lambda }^{-\frac{1}{2}}(t))} \\& \quad =\frac{y_{1}}{y_{1}-y_{2}} \frac{e_{\lambda }^{x_{1}+x_{2}}(t)}{1-y_{1}(e_{\lambda }^{\frac{1}{2}}(t)-e_{\lambda }^{-\frac{1}{2}}(t))}- \frac{y_{2}}{y_{1}-y_{2}} \frac{e_{\lambda }^{x_{1}+x_{2}}(t)}{1-y_{2}(e_{\lambda }^{\frac{1}{2}}(t)-e_{\lambda }^{-\frac{1}{2}}(t))} . \end{aligned}$$
(25)

By (22) and (25), we have

$$\begin{aligned}& \sum_{n=0}^{\infty }\binom{n}{k}F_{n-k,\lambda }^{(C)}(x_{1};y_{1})F_{k, \lambda }^{(C)}(x_{2};y_{2}) \frac{t^{n}}{n!} \\& \quad =\sum_{n=0}^{\infty } \biggl( \frac{y_{1}F_{n,\lambda }^{(C)}(x_{1}+x_{2};y_{1})-y_{2}F_{n,\lambda }^{(C)}(x_{1}+x_{2};y_{2})}{y_{1}-y_{2}} \biggr) \frac{t^{n}}{n!}. \end{aligned}$$
(26)

Therefore, by (26), we obtain the following theorem.

Theorem 4.4

Let n be a nonnegative integer with \(y_{1}\neq y_{2}\). The following formula holds true:

$$ \sum_{k=0}^{n}\binom{n}{k}F_{n-k,\lambda }^{(C)}(x_{1};y_{1})F_{k, \lambda }^{(C)}(x_{2};y_{2})= \frac{y_{1}F_{n,\lambda }^{(C)}(x_{1}+x_{2};y_{1})-y_{2}F_{n,\lambda }^{(C)}(x_{1}+x_{2};y_{2})}{y_{1}-y_{2}} . $$

Remark 4.1

Taking \(x_{1}=x_{2}=0\) in Theorem 4.4 reduces to

$$ \sum_{k=0}^{n}\binom{n}{k}F_{n-k,\lambda }^{(C)}(y_{1})F_{k, \lambda }^{(C)}(y_{2})= \frac{y_{1}F_{n,\lambda }^{(C)}(y_{1})-y_{2}F_{n,\lambda }^{(C)}(y_{2})}{y_{1}-y_{2}} . $$

Conclusion

In the present paper, we have considered type 2 degenerate central Fubini and type 2 degenerate central Fubini polynomials of two variables. We investigated some properties, identities and recurrence relations for these polynomials by making use of generating functions and p-adic fermionic integrals on \(\mathbb{Z}_{p}\). In addition, we have obtained some results related to degenerate central factorial numbers of the second kind and degenerate Euler numbers of the second kind.

Availability of data and materials

Not applicable.

References

  1. 1.

    Carlitz, L.: Degenerate Stirling, Bernoulli and Eulerian numbers. Util. Math. 15, 51–88 (1979)

    MathSciNet  MATH  Google Scholar 

  2. 2.

    Duran, U., Araci, S., Acikgoz, M.: A note on q-Fubini polynomials. Adv. Stud. Contemp. Math. 29, 211–224 (2019)

    MATH  Google Scholar 

  3. 3.

    Jang, G.-W., Kim, T.: A note on type 2 degenerate Euler and Bernoulli polynomials. Adv. Stud. Contemp. Math. (Kyungshang) 29(1), 147–159 (2019)

    MATH  Google Scholar 

  4. 4.

    Jang, L.-C., Kim, D.S., Kim, T., Lee, H.: p-Adic integral on \(\mathbb{Z} _{p}\) associated with degenerate Bernoulli polynomials of the second kind. Adv. Differ. Equ. 2020, 278 (2020)

    Article  Google Scholar 

  5. 5.

    Kargin, L.: Some formulae for products of Fubini polynomials with applications. arXiv:1701.01023v1 [math. CA] (2016)

  6. 6.

    Kilar, N., Simsek, Y.: A new family of Fubini type numbers and polynomials associated with Apostol–Bernoulli numbers and polynomials. J. Korean Math. Soc. 54(5), 1605–1621 (2017)

    MathSciNet  MATH  Google Scholar 

  7. 7.

    Kilar, N., Simsek, Y.: Identities and relations for Fubini type numbers and polynomials via generating functions and p-adic integral approach. Publ. Inst. Math. (Belgr.) 106(120), 113–123 (2019)

    MathSciNet  Article  Google Scholar 

  8. 8.

    Kim, D.S., Kim, T.: Some p-adic integrals on \(\mathbb{Z} _{p}\) associated with trigonometric functions. Russ. J. Math. Phys. 25(3), 300–308 (2018)

    MathSciNet  Article  Google Scholar 

  9. 9.

    Kim, D.S., Kim, T.: A note on a new type of degenerate Bernoulli numbers. Russ. J. Math. Phys. 27(2), 227–235 (2020)

    MathSciNet  Article  Google Scholar 

  10. 10.

    Kim, D.S., Kim, T., Lee, H.: A note on degenerate Euler and Bernoulli polynomials of complex variable. Symmetry 11(9), 1168 (2019)

    Article  Google Scholar 

  11. 11.

    Kim, D.S., Kwon, J., Dolgy, D.V., Kim, T.: On central Fubini polynomials associated with central factorial numbers of the second kind. Proc. Jangjeon Math. Soc. 21(4), 589–598 (2018)

    MathSciNet  MATH  Google Scholar 

  12. 12.

    Kim, T.: On the analogous of Euler numbers and polynomials associated with p-adic q-integrals on \(\mathbb{Z} _{p}\) at \(q=-1\). J. Math. Anal. Appl. 331(2), 779–792 (2007)

    MathSciNet  Article  Google Scholar 

  13. 13.

    Kim, T.: A note on degenerate Stirling polynomials of the second kind. Proc. Jangjeon Math. Soc. 20, 319–331 (2017)

    MathSciNet  MATH  Google Scholar 

  14. 14.

    Kim, T., Kim, D.S.: Degenerate Laplace transform and degenerate gamma function. Russ. J. Math. Phys. 24(2), 241–248 (2017)

    MathSciNet  Article  Google Scholar 

  15. 15.

    Kim, T., Kim, D.S.: Degenerate central factorial numbers of the second kind. Rev. R. Acad. Cienc. Exactas Fís. Nat., Ser. A Mat. 113, 3359–3367 (2019)

    MathSciNet  Article  Google Scholar 

  16. 16.

    Kim, T., Kim, D.S.: Note on the degenerate gamma function. Russ. J. Math. Phys. 27(3), 352–358 (2020)

    MathSciNet  Article  Google Scholar 

  17. 17.

    Kim, T., Kim, D.S.: A note on central bell numbers and polynomials. Russ. J. Math. Phys. 27(1), 76–81 (2020)

    MathSciNet  Article  Google Scholar 

  18. 18.

    Kim, T., Kim, D.S., Jang, G., Kim, D.: Two variable higher-order central Fubini polynomials. J. Inequal. Appl. 2019, 146 (2019)

    MathSciNet  Article  Google Scholar 

  19. 19.

    Kim, T., Kim, D.S., Jang, G.-W.: A note on degenerate Fubini polynomials. Proc. Jangjeon Math. Soc. 20(4), 521–531 (2017)

    MathSciNet  MATH  Google Scholar 

  20. 20.

    Kim, T., Kim, D.S., Jang, G.-W., Kwon, J.: Symmetric identities for Fubini polynomials. Symmetry 10(6), 219 (2018). https://doi.org/10.3390/sym10060219-14

    Article  MATH  Google Scholar 

  21. 21.

    Kim, T., Kim, D.S., Kim, H.-Y., Lee, H., Jang, L.-C.: Degenerate poly-Bernoulli polynomials arising from degenerate polylogarithm. Adv. Differ. Equ. 2020, 444 (2020)

    MathSciNet  Article  Google Scholar 

  22. 22.

    Kwon, J., Kim, W.J., Rim, S.-H.: On the some identities of the type 2 Daehee and Changhee polynomials arising from p-adic integrals on \(\mathbb{Z}_{p}\). Proc. Jangjeon Math. Soc. 22(3), 487–497 (2019)

    MathSciNet  MATH  Google Scholar 

  23. 23.

    Merca, M.: Connections between central factorial numbers and Bernoulli polynomials. Period. Math. Hung. 73(2), 259–264 (2016)

    MathSciNet  Article  Google Scholar 

  24. 24.

    Pyo, S.-S.: Some identities of degenerate Fubini polynomials arising from differential equations. J. Nonlinear Sci. Appl. 11(3), 383–393 (2018)

    MathSciNet  Article  Google Scholar 

Download references

Acknowledgements

We would like to thank the reviewers for their valuable suggestions and comments. We are also indebted to and thank Prof. Dr. Dae San Kim at Sogang University (South Korea) for his valuable suggestions and comments.

Funding

The authors would like to thank the Deanship of Scientific Research at Majmaah University for supporting this work under project number No. R-1441-169.

Author information

Affiliations

Authors

Contributions

All authors contributed equally to this article. All authors read and approved the final manuscript.

Corresponding author

Correspondence to Sunil Kumar Sharma.

Ethics declarations

Competing interests

The authors declare that they have no competing interests.

Rights and permissions

Open Access This article is licensed under a Creative Commons Attribution 4.0 International License, which permits use, sharing, adaptation, distribution and reproduction in any medium or format, as long as you give appropriate credit to the original author(s) and the source, provide a link to the Creative Commons licence, and indicate if changes were made. The images or other third party material in this article are included in the article’s Creative Commons licence, unless indicated otherwise in a credit line to the material. If material is not included in the article’s Creative Commons licence and your intended use is not permitted by statutory regulation or exceeds the permitted use, you will need to obtain permission directly from the copyright holder. To view a copy of this licence, visit http://creativecommons.org/licenses/by/4.0/.

Reprints and Permissions

About this article

Verify currency and authenticity via CrossMark

Cite this article

Sharma, S.K., Khan, W.A., Araci, S. et al. New construction of type 2 degenerate central Fubini polynomials with their certain properties. Adv Differ Equ 2020, 587 (2020). https://doi.org/10.1186/s13662-020-03055-4

Download citation

  • Received:

  • Accepted:

  • Published:

  • DOI: https://doi.org/10.1186/s13662-020-03055-4

MSC

  • 11B68
  • 11B83
  • 11S80

Keywords

  • Fubini polynomials
  • Degenerate central Fubini polynomials
  • Degenerate central factorial numbers of the second kind
  • Poly-Frobenius–Genocchi polynomials